Giant Left Ventricular Thrombus in a Patient with Acute Ischemic Stroke: A Case Report and Minireview - Fan Ye; Burton V. Silverstein; Matheen A. Khuddus; Christopher L. Bray; Arthur C. Lee (Case Reports in Cardiology)
A 56-year-old healthy male with no obvious risk factors or significant past medical history was admitted to the emergency room with acute ischemic stroke. On his transthoracic echocardiography (TTE), an extremely large thrombus was detected at the apex involving the distal anterior wall. The thrombus was predominantly adherent but with a mobile tip. The patient was subsequently managed with dual antiplatelet therapy. In this report, we present an interesting case of an acute ischemic stroke secondary to a giant left ventricular thrombus in a patient with no past significant cardiac or neurologic medical history.